2000
DOI: 10.1046/j.1365-2265.2000.00943.x
|View full text |Cite
|
Sign up to set email alerts
|

The application of a combined stimulation with CRH and desmopressin during bilateral inferior petrosal sinus sampling in patients with Cushing's syndrome

Abstract: A combined stimulus using CRH and desmopressin appears to induce a higher ACTH output from pituitary corticotroph adenomas during BIPSS, which may improve the diagnostic sensitivity of this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…Previous studies have shown the potential interest of the vasopressin (AVP) analog desmopressin in the diagnosis of Cushing's disease due to an overexpression of the V1b/V3 subtype of the arginine vasopressin receptor in adenomatous vs normal corticotroph cells (24,33). Indeed, taking together the results from several studies in a total of 192 subjects with Cushing's disease, a positive cortisol response to desmopressin was reported on average in 92% of patients, and an ACTH response in 85% (17,25,26,30,31,34). Definitions for positive response may, however, differ slightly between authors who also used different assays with distinct characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the potential interest of the vasopressin (AVP) analog desmopressin in the diagnosis of Cushing's disease due to an overexpression of the V1b/V3 subtype of the arginine vasopressin receptor in adenomatous vs normal corticotroph cells (24,33). Indeed, taking together the results from several studies in a total of 192 subjects with Cushing's disease, a positive cortisol response to desmopressin was reported on average in 92% of patients, and an ACTH response in 85% (17,25,26,30,31,34). Definitions for positive response may, however, differ slightly between authors who also used different assays with distinct characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the CRH test, introduced in the IPSS procedure to create an ACTH pulse and thus minimize the IPS:P ratio distortion due to interpulse intervals (6,27), seems to achieve the maximal sensitivity, negative predictivity and diagnostic accuracy when the cumulative response to both basal and stimulated test was used. The diagnostic accuracy of IPSS seems to be further improved by using a combined stimulus with CRH and desmopressin (28).…”
Section: Discussionmentioning
confidence: 99%
“…The first (nZ26 patients with CD and 4 with EAS) tried to compare the use of CRH with desmopressin during bilateral petrosal sinus samplingthe procedure showed an accuracy of about 90% of cases in differentiating CD and ectopic ACTH secretion (25). The second (nZ56 patients, 5 EAS) found a sensitivity of 92% and a specificity of 100% (26).…”
Section: Figurementioning
confidence: 99%